Standardised computed tomographic assessment of left atrial morphology and tissue thickness in humans. (February 2021) - Whitaker, John; Karády, Júlia; Karim, Rashed; Tobon-Gomez, Catalina; Fastl, Thomas; Razeghi, Orod; O'Neill, Louisa; Decroocq, Marie; Williams, Steven; Corrado, Cesare; Mukherjee, Rahul K.; Sim, Iain; et al.
Abstract: Aims: Left atrial (LA) remodelling is a common feature of many cardiovascular pathologies and is a sensitive marker of adverse cardiovascular outcomes. The aim of this study was to establish normal ranges for LA parameters derived from coronary computed tomographic angiography (CCTA) imaging using a standardised image processing pipeline to establish normal ranges in a previously described cohort. Methods: CCTA imaging from 193 subjects recruited to the Budapest GLOBAL twin study was analysed. Indexed LA cavity volume (LACVi ), LA surface area (LASAi ), wall thickness and LA tissue volume (LATVi ) were calculated. Wall thickness maps were combined into an atlas. Indexed LA parameters were compared with clinical variables to identify early markers of pathological remodelling. Results: LACVi is similar between sexes (31 ml/m 2 v 30 ml/m 2 ) and increased in hypertension (33 ml/m 2 v 29 ml/m 2, p = 0.009). LASAi is greater in females than males (47.8 ml/m 2 v 45.8 ml/m 2 male, p = 0.031). Median LAWT was 1.45 mm. LAWT was lowest at the inferior portion of the posterior LA wall (1.14 mm) and greatest in the septum (median = 2.0 mm) (p < 0.001). Conditions known to predispose to the development of AF were not associated with differences in tissue thickness. Conclusions: The reported LACVi, LASAi, LATVi and tissue thickness derived from CCTA may serve as reference values for this age group and clinical characteristics for future studies. Increased LASAi in females in the absence of differences in LACVi or LATVi may indicate differential LA shape changes between the sexes. AF predisposing conditions, other than sex, were not associated with detectable changes in LAWT. Clinical trial registration: http://www.ClinicalTrials.gov/NCT01738828 .